Retrieval of atmospheric parameters and data-processing algorithms for AVIRIS-NG Indian campaign data - Mishra, Manoj K.; Gupta, Anurag; John, Jinya; Shukla, Bipasha P.; Dennison, Philip; Srivastava, S. S.; Kaushik, Nitesh K.; Misra, Arundhati; Dhar, D. (Current science (Bangalore), 2019)
Applications of high-spatial resolution imaging spectrometer data acquired from the Airborne Visible/Infrared Imaging Spectrometer-Next Generation (AVIRIS-NG) under India campaign 2015–16, require a thorough compensation for atmospheric absorption and scattering. The data-processing algorithms used for retrieving critically important atmospheric parameters, namely ‘water vapour and aerosol optical depth (AOD)’ over land and water surfaces are presented. Over land surfaces, the dark dense vegetation method and radiative transfer modelling are used for deriving spectral AOD for boxes of 20 × 20 pixels. For AOD retrieval over water surfaces, dark-target approximation is used with near-infrared and short-wave infrared measurements. Estimation of precipitable water vapour is carried out using short-wave hyperspectral measurements for each pixel. A differential absorption technique (continuum interpolated band ratio) has been used for this purpose. The retrieved AOD and water vapour values were compared with in situ sun-photometer and radiosonde data respectively, indicating good matches. Further, these parameters were used to derive ‘atmospherically corrected surface reflectance and remote sensing reflectance’, for land and water surface respectively, assuming horizontal surfaces having Lambertian reflectance.